2012
DOI: 10.1111/j.1476-5829.2012.00336.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between symptomatic treatment and lomustine supplementation in 71 dogs with intracranial, space‐occupying lesions

Abstract: Brain neoplasia is diagnosed in an increasing number of dogs. Consequently, there is a higher need for an effective treatment. Chemotherapy is considered in cases where surgery or radiation is not optional. The objective of this retrospective study was to evaluate the difference in median survival time (MST) of dogs with intracranial masses, treated symptomatically with corticosteroids and anti-epileptic drugs, compared with the same symptomatic treatment supplemented with lomustine. The records of 71 dogs wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
64
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 31 publications
6
64
0
5
Order By: Relevance
“…Almost all studies lack histologic diagnoses for most cases, and thus have limited value. A large retrospective study suggested no benefit for CT‐defined brain masses from lomustine (CCNU) chemotherapy compared to palliative care (93 days versus 60 days), but none of the 71 animals had a histologic diagnosis 142. Anecdotal histologically confirmed cases from published data show apparent survival benefits and occasional responses with survival of many months in some cases, but overall, chemotherapy alone appears to have limited value for intracranial tumors 147, 154, 166, 167, 168, 169.…”
Section: Chemotherapymentioning
confidence: 99%
“…Almost all studies lack histologic diagnoses for most cases, and thus have limited value. A large retrospective study suggested no benefit for CT‐defined brain masses from lomustine (CCNU) chemotherapy compared to palliative care (93 days versus 60 days), but none of the 71 animals had a histologic diagnosis 142. Anecdotal histologically confirmed cases from published data show apparent survival benefits and occasional responses with survival of many months in some cases, but overall, chemotherapy alone appears to have limited value for intracranial tumors 147, 154, 166, 167, 168, 169.…”
Section: Chemotherapymentioning
confidence: 99%
“…A recent study failed to demonstrate any difference in survival between dogs with brain tumors treated symptomatically with prednisone and anticonvulsant drugs compared with those that received symptomatic therapy and lomustine. 20 There is increasing recognition of the epidemiologic, neuropathologic, molecular, and genetic homologies between canine and human brain tumors, which has driven the use of dogs with spontaneous brain tumors as a translational disease model. [21][22][23] This review introduces contemporary therapeutic advancements for brain tumors and illustrates the role that tumor-bearing dogs have made to progressing the field of translational neuro-oncology.…”
Section: Introductionmentioning
confidence: 99%
“…Anecdotal published data show apparent survival benefits and occasional responses with survival of many months in some cases (Jung et al, 2006;Tamura et al, 2007). However, a large retrospective study suggested no benefit from lomustine chemotherapy compared to palliative care (93 days versus 60 days) for brain masses diagnosed via computed tomography and without a histologic diagnosis (Van Meervenne and Verhoeven, 2014). Radiation therapy has become a mainstay of treatment for intracranial neoplasia in both human and veterinary patients, either as a primary or adjunctive treatment (Dickinson, 2014).…”
Section: Introductionmentioning
confidence: 99%